Using gender to undo gender A feminist degendering movement - Judith Lorber (Feminist Theory 1(1) 2000, 2000)
Women's status in the Western world has improved enormously, but the revolution that would make women and men truly equal has not yet occurred. I argue that the reason is that gender divisions still deeply bifurcate the structure of modern society. Feminists want women and men to be equal, but few talk about doing away with gender divisions altogether. From a social constructionist structural gender perspective, it is the ubiquitous division of people into two unequally valued categories that undergirds the continually reappearing instances of gender inequality. I argue that it is this gendering that needs to be challenged by feminists, with the long-term goal of doing away with binary gender divisions altogether. To this end, I call for a feminist degendering movement